CIRCumcision learning experience using simulation: A pilot learning platform for safe neonatal circumcision training offered either virtually or in person - Dos Santos, Joana; Alsabban, Abdulrahman; Maizels, Max; Chua, Michael; Vuppal, Sunayna; Louca, Emily; Perlmutar, Martin; Knabl, Jennifer; Rickard, Mandy; Varghese, Abby; Lorenzo, Armando J.; Koyle, Martin Allan (Frontiers in Urology, 2023)
Through an innovative 3-step simulation training platform for neonatal circumcision developed during the COVID pandemic, this study demonstrated similar efficacy for virtual and in-person learners.Neonatal circumcision is one of the most common surgical procedures performed worldwide. It can be associated with avoidable complications, particularly with less experienced practitioners. However, there are no formal, structured training programs for practitioners performing this procedure.Our simulation training platform showed significant improvement in learners' knowledge, skills, and confidence in performing neonatal circumcision in both groups (virtual and inperson). This can potentially decrease the risk of the avoidable complications associated with this procedure.